The Depiction of Narcissistic Personality Disorder of Elizabeth Halsey as Found in "Bad Teacher" Movie - Diana Zuriati; Lelly Zuyana Asril; Abdel Chaleed Mahawangsa (Enlighted Journal, 2024)
Narcis Narcisism gained attention and discussion in recent years. This was caused by the rise of social media facilitating self-promotion and self-expression on a massive scale so that narcissistic behaviours can be seen more and more obvious. It could become a problem when they were excessive, inflexible, and maladaptive, leading to harm or distress to individuals or those around them. These extreme traits can be classified as Narcissistic Personality Disorder (NPD). This study aimed to describe the narcissistic's trait of Elizabeth Halsey in Bad Teacher Movie. Elizabeth Halsey worked as a teacher who should demonstrate empathy by understanding her students' perspectives, needs, and emotions, how she can creates a safe and supportive learning environment where students feel valued and heard but her character as a teacher showed narcissistic  traits that are the opposite of what a teacher should have. This research used a psychoanalysis approach. The method of this research was qualitative method. In collecting the data, the researchers watched the movie, marking  and classifying in what kinds of types of traits that the Elizabeth Halsey had. In analyzing the data, the researchers used descriptive method firstly by identifying all the statements that describe the types of the traits faced by Elizabeth Halsey, and then analyzed the data based on the finding. The results of this study found that there were four of nine traits of narcissistic in Elizabeth Halsey's Character. The first is entitlement trait, she only thought about herself, she did not have any shame on herself, she still asked money from her ex fiance. The second was exploitative traits, in this case, Elizabeth Halsey took advantage on many people, she would do everything without thinking's other feelings and opinion. The third was lack of empathy, she did not showed any empathy for her students who got bullied in front of her, and the last was envy trait, she did  not accept the reality that the wealthy man fell in love with her enemy at school, she arranged everything to make her enemy kicked out from school.